Private sector delivery of quality care for maternal, newborn and child health in low-income and middle-income countries: a mixed-methods systematic review protocol - Lattof, Samantha R (BMJ Open, 2020)
INTRODUCTION: To accelerate progress to reach the sustainable development goals for ending preventable maternal, newborn and child deaths, it is critical that both the public and private health service delivery systems invest in increasing coverage of interventions to sustainably deliver quality care for mothers, newborns and children at scale. Although various approaches have been successful in high-income countries, little is known about how to effectively engage and sustain private sector involvement in delivering quality care in low-income and middle-income countries. Our systematic review will examine private sector implementation of quality care for maternal, newborn and child health (MNCH) and the impact of this care. This protocol details our intended methodological and analytical approaches, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guideline for protocols. METHODS AND ANALYSIS: Following the PRISMA approach, this systematic review will include quantitative, qualitative and mixed-methods studies addressing the provision of quality MNCH care by private sector providers. Eight databases (Cumulative Index to Nursing and Allied Health, EconLit, Excerpta Medica Database, International Bibliography of the Social Sciences, Popline, PubMed, ScienceDirect, Web of Science) and two websites will be searched for relevant studies published between 1 January 1995 and 30 June 2019. For inclusion, studies in low-income and middle-income countries must examine at least one of the following critical outcomes: maternal morbidity or mortality, newborn morbidity or mortality, child morbidity or mortality, quality of care, experience of care and service utilisation. Depending on the data, analyses could include meta-analysis, descriptive quantitative statistics, narrative synthesis and thematic synthesis. Quality will be assessed using tools for qualitative and quantitative studies. ETHICS AND DISSEMINATION: Formal ethical approval is not required for this research, as the secondary data are not identifiable. Findings from this review will be used to develop models for effective collaboration of the private and public sectors in implementing quality of care for MNCH. In addition to publishing our findings in a peer-reviewed journal, the findings will be shared through the Quality of Care Network, relevant mailing lists, webinars and social media. PROSPERO REGISTRATION NUMBER: CRD42019143383